High-energy high-burning-rate hydroxyl-terminated polybutadiene propellant containing coated aluminum powder and DAP-4 and preparation method of high-energy high-burning-rate hydroxyl-terminated polybutadiene propellant
By using coated aluminum powder and DAP-4 in butyl hydroxy propellant, the problem of difficult to improve the specific impulse and combustion speed of the existing propellant is solved, and the combustion speed and energy performance are significantly improved, and the application scope is expanded.
Patent Information
- Application Number
- CN202411789385.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
The specific impulse and combustion speed of existing hydroxyl propellants is difficult to further improve, limiting the performance and scope of use of rockets and missiles.
The coated aluminum powder and DAP-4 are used to replace traditional micron aluminum and high-energy nitramine explosives, and the energy performance and combustion efficiency of the propellant are improved by improving the structure and composition of the combustion agent.
It significantly improves the combustion speed and energy performance of hydroxyl propellant, meets the requirements of high-fuel speed hydroxyl propellant, and expands its application range in the fields of rockets and missiles.
Smart Images

Figure BDA0005174945940000071 
Figure BDA0005174945940000081 
Figure BDA0005174945940000082
Abstract
Description
Technical Field
[0001] The invention belongs to the field of explosives and in particular relates to a high-energy and high-burning-rate hydroxybutyric acid propellant containing coated aluminum powder and DAP-4 and a preparation method thereof. Background Art
[0002] Hydroxyl-terminated polybutadiene propellant, referred to as hydroxybutadiene propellant, is a solid propellant composed of hydroxyl-terminated polybutadiene (HTPB) as a binder, diisocyanate as a curing agent, ammonium perchlorate (AP) as an oxidant, micron aluminum powder (μAl) as a combustion agent, and high-energy nitramine explosive as an energy additive. sp ) is generally between 250 and 266 seconds, the burning rate under 7MPa pressure is generally between 8 and 15mm / s, and the burning rate-pressure index is generally around 0.3 to 0.5. Due to its high energy, good mechanical properties, and stable combustion, most of the strategic and tactical missile engines in service and under development at home and abroad currently use this propellant, and even the high-thrust boosters used to launch space shuttles use HTPB propellant. In fact, although the preparation technology of HTPB propellant is very mature at present, research on its modification is still emerging in an endless stream. For example, in domestic and foreign research, continuing to improve the specific impulse and burning rate of HTPB propellant has always been a hot direction. High energy means that rockets and missiles can shoot high and hit far; and high burning rate not only means that the engine increases thrust while the charge and structure remain unchanged, but also means expanding the scope of use of HTPB propellant.
[0003] In terms of specific impulse, the combination of HTPB, AP and μAl and the energy released by their combustion are the main energy sources of the propellant. High-energy nitramine explosives usually increase the specific impulse of HTPB propellant by increasing the nitrogen content in the propellant combustion products under the conditions of high formation enthalpy and high combustion heat. At present, in order to ensure the mechanical properties and combustion performance of the propellant in the optimal state, the properties and mass fractions of HTPB, AP and μAl are usually fixed and cannot be easily changed; what can be replaced is high-energy nitramine explosives. Therefore, replacing nitramine explosives such as hexogen (RDX), octogen (HMX) and hexanitrohexaazaisowurtzitane (CL-20) with substances with higher energy is a feasible method to improve the energy performance of HTPB propellant. The molecular perovskite energetic material DAP-4 synthesized in recent years has application prospects in this regard.
[0004] Molecular perovskite energetic materials are a new type of energetic ion salt with an ABX3 structure. Academician Chen Xiaoming of Sun Yat-sen University first designed and synthesized this high-energy material with a molecular structure in 2018. A is a protonated triethylenediamine cation (H2dabco 2+ , namely C6H 14 N2 2+ ), B can take NH4+ , K + 、Na + 、Ag + Equivalent cations, X can be ClO4 - 、NO3 - IO4 - Therefore, this ABX3 structured energetic material is different from traditional pyrotechnic propellants. It cleverly combines the fuel (H2dabco) commonly used in propellants or pyrotechnic agents 2+ ) and oxidant (ClO4 - ) are combined in one molecule, creating optimal conditions for the redox reaction between them. In particular, when B takes NH4 + When the cation is + It does not contain metal ions and can also be used as a fuel with ClO4 - The reaction generates a large amount of gas and heat, resulting in (H2dabco)[NH4(ClO4)3] (i.e., DAP-4) being the most energetic molecular perovskite energetic material. Specifically, the chemical formula of DAP-4 is (C6H 14 N2)[NH4(ClO4)3], molecular weight is 430.6g / mol, density is 1.87g / cm 3 , oxygen balance is OB CO =-5.6%, OB CO2 =-27.9%, and the formation enthalpy is +278.6kJ / mol. Its theoretical detonation velocity reaches 8597m / s, which is basically the same as the detonation velocity of RDX. The theoretical detonation heat and detonation pressure of DAP-4 are -6879kJ / kg and 35.6GPa, which are the highest among the known energetic materials. DAP-4 has a low sensitivity, and its impact sensitivity is H 50 =112.3cm (2kg drop hammer), friction sensitivity is P=45% (2kg pendulum, 90o swing angle, 3.50MPa pressure), and electrostatic sensitivity is 5.39J, so its sensitivity is much lower than RDX, HMX and CL-20. At the same time, DAP-4 is also non-hygroscopic. In addition, DAP-4 has good chemical compatibility with the commonly used components in hydroxybutyl propellant. From the perspective of solid propellants, DAP-4 is an excellent high-energy filler because its unit propellant standard specific impulse reaches I sp =289s (NASA-CEA2 calculation, P c =7.0MPa, P e =0.1MPa, T0=298K, ΔH f,DAP-4 = +278.6 kJ / mol), while under the same conditions, the standard specific impulses of RDX, HMX and CL-20 are only I sp=266s, 265s and 273s. Therefore, replacing RDX, HMX or CL-20 with DAP-4 is expected to improve the energy performance of HTPB propellant.
[0005] In terms of burning rate, the low oxidation efficiency of aluminum powder and the slow decomposition and combustion rate of nitramine explosives play a limiting role. The average particle size of μAl used in HTPB propellant is usually d 50 =15~25μm. As we all know, at room temperature and pressure, the surface of μAl particles is coated with a dense oxide layer, and the melting point and boiling point of this oxide layer are 2054℃ and 2980℃ respectively. As long as the oxide layer is not broken, the metal active aluminum cannot come into contact with the oxidant to undergo oxidation or combustion reaction. Therefore, its existence largely restricts the reaction between μAl and the oxidant, causing the ignition temperature of μAl to reach above 2200℃. In addition, considering the requirements of the propellant preparation process performance and combustion performance, the particle size of μAl must be controlled between 15 and 25μm. Such large aluminum particles, restricted by the surface oxide layer, cannot be fully burned in the engine combustion chamber, resulting in poor combustion efficiency, which causes the problem of difficulty in further improving the burning rate. The coated aluminum powder used in the present invention has a special core-shell structure, that is, a layer of transition metal nanoparticles is coated on the surface of the active metal aluminum, and its oxidation process mechanism is significantly different from that of the raw material μAl powder. Oxygen from the outside can not only easily pass through the loose metal shell to reach the surface of the active aluminum, but also through the aluminothermic reaction, with the metal shell as a "bridge", to "relay" the oxygen at the interface of the core and shell. By breaking the restriction of the alumina layer, this coating greatly reduces the starting temperature of the oxidation reaction of μAl and greatly increases the heat release rate during the oxidation reaction (reference: "Wang Yi, et al. Preparation of core-shell structured Ni(Cu,Co) / Al micro-nano composite particles and characterization of their thermal reaction performance with Fe2O3 [J]. Rare Metal Materials and Engineering, 2008, 37(7): 1197-1200."), thus it is expected to increase the burning rate of HTPB propellant. Summary of the invention
[0006] The purpose of the present invention is to provide a high-energy and high-burning-rate HTPB propellant containing coated aluminum powder and DAP-4 and a preparation method thereof.
[0007] The present invention is achieved through the following technical solutions:
[0008] The invention relates to a high-energy and high-burning-rate hydroxybutadiene propellant containing coated aluminum powder and DAP-4. The propellant comprises the following components in percentage by mass: 16 wt.% of terminal hydroxyl polybutadiene (HTPB), 18 wt.% of coated aluminum powder, 54 wt.% of ammonium perchlorate, 10 wt.% of high-energy explosive and 2 wt.% of toluene diisocyanate (TDI).
[0009] Preferably, the coated aluminum powder is μAl coated with nano-Ni, i.e., nNi / μAl; or μAl coated with nano-Ni and nano-Cu, i.e., [nNi+nCu] / μAl; or μAl coated with nano-Ni, nano-Cu and nano-Fe, i.e., [nNi+nCu+nFe] / μAl; or μAl coated with nano-Ni, nano-Cu, nano-Fe and nano-Co, i.e., [nNi+nCu+nFe+nCo] / μAl. For all preparation methods and properties of coated aluminum powder, please refer to: "Wang Yi, et al. Preparation method of multi-transition metal coated micron aluminum composite fuel [P]. Chinese invention patent, ZL 202111123467.1".
[0010] Preferably, the hydroxy-terminated polybutadiene is a binder, and at 25° C., its viscosity ranges from 2 to 4 Pa·s, and its hydroxyl value ranges from 1.5 to 2.0 mmol / g.
[0011] Preferably, the particle size of the ammonium perchlorate is 100-200 μm.
[0012] Preferably, the high-energy explosive is DAP-4. The preparation method and properties of DAP-4 are described in the reference: "Chen Kangyu, Song Xiaolan, Wang Yi, et al. Characterization and performance study of molecular perovskite energetic material DAP-4 [J]. Journal of Explosives and Propellants, 2024, 47(9): 786-796.".
[0013] The present invention also relates to a method for preparing the aforementioned high-energy and high-burning-rate HTPB propellant containing coated aluminum powder and DAP-4, comprising the following steps:
[0014] (1) Add an appropriate amount of hydroxyl-terminated polybutadiene (HTPB) into a 1L small kneader, start the kneader, and knead slowly;
[0015] (2) adding an appropriate amount of coated aluminum powder to a kneader, kneading for 10 minutes, then slowly adding an appropriate amount of ammonium perchlorate (AP) to the kneader, kneading for 10 minutes, then adding an appropriate amount of high-energy explosive to the kneader, kneading for 10 minutes, then adding a small amount of toluene diisocyanate (TDI) to the kneader, closing the kneader, evacuating, and kneading for 45 minutes, then stopping the kneading and ventilating;
[0016] (3) The kneaded slurry was injected into a square aluminum box and cured in an oven at 60° C. for 15 days to obtain a solid propellant block;
[0017] (4) Cut the block into strips using a cutting machine, and then coat the outer surface of the strip propellant with a layer of polyvinyl alcohol;
[0018] The above components are taken according to the following mass percentages: 16wt.% of terminal hydroxyl polybutadiene (HTPB), 18wt.% of coated aluminum powder, 54wt.% of ammonium perchlorate, 10wt.% of high energy explosive, and 2wt.% of toluene diisocyanate (TDI).
[0019] The present invention has the following advantages:
[0020] (1) The DAP-4 used in the present invention is a high-energy explosive with an extremely fast burning rate, which is 3 to 5 times that of RDX, HMX or CL-20. In thermal analysis tests, 10 mg of RDX, HMX or CL-20 can be thermally decomposed quietly and slowly at a heating rate of 5°C / min; while 1 mg of DAP-4 will detonate under the same test conditions. Therefore, during the test, the amount of DAP-4 must be controlled within 0.5 mg so that it can barely decompose normally instead of detonating. This experimental phenomenon shows that the decomposition and burning rates of DAP-4 are much higher than those of RDX, HMX or CL-20. Therefore, the present invention uses DAP-4 in hydroxybutyric acid propellant to help improve the burning rate of the propellant.
[0021] (2) After the present invention replaces the "micron aluminum" and "high-energy nitramine explosive" in the traditional HTPB propellant with "coated aluminum" and "DAP-4" respectively, the burning rate of the HTPB propellant prepared by the present invention is significantly improved while the mass ratio remains unchanged, and the burning rate at 7MPa meets the requirements of the high burning rate HTPB propellant.
[0022] (3) The hydroxybutyric acid propellant prepared by the present invention has the characteristics of high energy and high burning rate. DETAILED DESCRIPTION
[0023] The present invention is described in detail below in conjunction with specific embodiments. It should be noted that the following embodiments are only further descriptions of the present invention, but the protection scope of the present invention is not limited to the following embodiments.
[0024] Example 1
[0025] First, add 160 g of hydroxyl-terminated polybutadiene (HTPB) into a 1 L small kneader, start the kneader, and knead slowly;
[0026] Then, 180 g of nNi / μAl was added to the kneader. After kneading for 10 minutes, 540 g of ammonium perchlorate (AP) was slowly added to the kneader. After kneading for 10 minutes, 100 g of DAP-4 was added to the kneader. After kneading for 10 minutes, 20 g of toluene diisocyanate (TDI) was added to the kneader. The kneader was closed and vacuumed. After continuing kneading for 45 minutes, kneading was stopped and air was allowed to pass.
[0027] The kneaded slurry was then injected into a square aluminum box and cured in an oven at 60°C for 15 days to obtain a solid propellant block.
[0028] Finally, the block is cut into strips using a cutting machine, and then a layer of polyvinyl alcohol is coated on the surface of the propellant strips to finally obtain propellant strips that can be tested for combustion performance.
[0029] Example 2
[0030] First, add 160 g of hydroxyl-terminated polybutadiene (HTPB) into a 1 L small kneader, start the kneader, and knead slowly;
[0031] Then, 180 g of [nNi+nCu] / μAl was added to the kneader, and after kneading for 10 minutes, 540 g of ammonium perchlorate (AP) was slowly added to the kneader, and after kneading for 10 minutes, 100 g of DAP-4 was added to the kneader, and after kneading for 10 minutes, 20 g of toluene diisocyanate (TDI) was added to the kneader, and the kneader was closed and evacuated, and after kneading for 45 minutes, kneading was stopped and air was ventilated;
[0032] The kneaded slurry was then injected into a square aluminum box and cured in an oven at 60°C for 15 days to obtain a solid propellant block.
[0033] Finally, the block is cut into strips using a cutting machine, and then a layer of polyvinyl alcohol is coated on the surface of the propellant strips to finally obtain propellant strips that can be tested for combustion performance.
[0034] Example 3
[0035] First, add 160 g of hydroxyl-terminated polybutadiene (HTPB) into a 1 L small kneader, start the kneader, and knead slowly;
[0036] Then, 180 g of [nNi+nCu+nFe] / μAl was added to the kneader, and after kneading for 10 minutes, 540 g of ammonium perchlorate (AP) was slowly added to the kneader, and after kneading for 10 minutes, 100 g of DAP-4 was added to the kneader, and after kneading for 10 minutes, 20 g of toluene diisocyanate (TDI) was added to the kneader, and the kneader was closed and evacuated, and after kneading for 45 minutes, kneading was stopped and air was ventilated;
[0037] The kneaded slurry was then injected into a square aluminum box and cured in an oven at 60°C for 15 days to obtain a solid propellant block.
[0038] Finally, the block is cut into strips using a cutting machine, and then a layer of polyvinyl alcohol is coated on the surface of the propellant strips to finally obtain propellant strips that can be tested for combustion performance.
[0039] Example 4
[0040] First, add 160 g of hydroxyl-terminated polybutadiene (HTPB) into a 1 L small kneader, start the kneader, and knead slowly;
[0041] Then, 180 g of [nNi+nCu+nFe+nCo] / μAl was added to the kneader, and after kneading for 10 minutes, 540 g of ammonium perchlorate (AP) was slowly added to the kneader, and after kneading for 10 minutes, 100 g of DAP-4 was added to the kneader, and after kneading for 10 minutes, 20 g of toluene diisocyanate (TDI) was added to the kneader, and the kneader was closed and evacuated, and after kneading for 45 minutes, kneading was stopped and air was ventilated;
[0042] The kneaded slurry was then injected into a square aluminum box and cured in an oven at 60°C for 15 days to obtain a solid propellant block.
[0043] Finally, the block is cut into strips using a cutting machine, and then a layer of polyvinyl alcohol is coated on the surface of the propellant strips to finally obtain propellant strips that can be tested for combustion performance.
[0044] Comparative Example 1
[0045] First, add 160 g of hydroxyl-terminated polybutadiene (HTPB) into a 1 L small kneader, start the kneader, and knead slowly;
[0046] Then, 180 g of the raw material μAl was added to the kneader, and after kneading for 10 minutes, 540 g of ammonium perchlorate (AP) was slowly added to the kneader, and after kneading for 10 minutes, 100 g of RDX was added to the kneader, and after kneading for 10 minutes, 20 g of toluene diisocyanate (TDI) was added to the kneader, and the kneader was closed and evacuated, and after kneading for 45 minutes, the kneading was stopped and air was ventilated;
[0047] The kneaded slurry was then injected into a square aluminum box and cured in an oven at 60°C for 15 days to obtain a solid propellant block.
[0048] Finally, the block is cut into strips using a cutting machine, and then a layer of polyvinyl alcohol is coated on the surface of the propellant strips to finally obtain propellant strips that can be tested for combustion performance.
[0049] Comparative Example 2
[0050] First, add 160 g of hydroxyl-terminated polybutadiene (HTPB) into a 1 L small kneader, start the kneader, and knead slowly;
[0051] Then, 180 g of the raw material μAl was added to the kneader, and after kneading for 10 minutes, 540 g of ammonium perchlorate (AP) was slowly added to the kneader, and after kneading for 10 minutes, 100 g of HMX was added to the kneader, and after kneading for 10 minutes, 20 g of toluene diisocyanate (TDI) was added to the kneader, and the kneader was closed and evacuated, and after kneading for 45 minutes, kneading was stopped and air was ventilated;
[0052] The kneaded slurry was then injected into a square aluminum box and cured in an oven at 60°C for 15 days to obtain a solid propellant block.
[0053] Finally, the block is cut into strips using a cutting machine, and then a layer of polyvinyl alcohol is coated on the surface of the propellant strips to finally obtain propellant strips that can be tested for combustion performance.
[0054] Comparative Example 3
[0055] First, add 160 g of hydroxyl-terminated polybutadiene (HTPB) into a 1 L small kneader, start the kneader, and knead slowly;
[0056] Then, 180 g of the raw material μAl was added to the kneader, and after kneading for 10 minutes, 540 g of ammonium perchlorate (AP) was slowly added to the kneader, and after kneading for 10 minutes, 100 g of CL-20 was added to the kneader, and after kneading for 10 minutes, 20 g of toluene diisocyanate (TDI) was added to the kneader, and the kneader was closed and evacuated, and after kneading for 45 minutes, kneading was stopped and air was ventilated;
[0057] The kneaded slurry was then injected into a square aluminum box and cured in an oven at 60°C for 15 days to obtain a solid propellant block.
[0058] Finally, the block is cut into strips using a cutting machine, and then a layer of polyvinyl alcohol is coated on the surface of the propellant strips to finally obtain propellant strips that can be tested for combustion performance.
[0059] Comparative Example 4
[0060] First, add 160 g of hydroxyl-terminated polybutadiene (HTPB) into a 1 L small kneader, start the kneader, and knead slowly;
[0061] Then, 180 g of the raw material μAl was added to the kneader, and after kneading for 10 minutes, 540 g of ammonium perchlorate (AP) was slowly added to the kneader, and after kneading for 10 minutes, 100 g of DAP-4 was added to the kneader, and after kneading for 10 minutes, 20 g of toluene diisocyanate (TDI) was added to the kneader, and the kneader was closed and evacuated, and after kneading for 45 minutes, the kneading was stopped and air was ventilated;
[0062] The kneaded slurry was then injected into a square aluminum box and cured in an oven at 60°C for 15 days to obtain a solid propellant block.
[0063] Finally, the block is cut into strips using a cutting machine, and then a layer of polyvinyl alcohol is coated on the surface of the propellant strips to finally obtain propellant strips that can be tested for combustion performance.
[0064] Comparative Example 5
[0065] First, add 160 g of hydroxyl-terminated polybutadiene (HTPB) into a 1 L small kneader, start the kneader, and knead slowly;
[0066] Then, 180 g of [nNi+nCu+nFe+nCo] / μAl was added to the kneader, and after kneading for 10 minutes, 540 g of ammonium perchlorate (AP) was slowly added to the kneader, and after kneading for 10 minutes, 100 g of RDX was added to the kneader, and after kneading for 10 minutes, 20 g of toluene diisocyanate (TDI) was added to the kneader, and the kneader was closed and evacuated, and after kneading for 45 minutes, kneading was stopped and air was ventilated;
[0067] The kneaded slurry was then injected into a square aluminum box and cured in an oven at 60°C for 15 days to obtain a solid propellant block.
[0068] Finally, the block is cut into strips using a cutting machine, and then a layer of polyvinyl alcohol is coated on the surface of the propellant strips to finally obtain propellant strips that can be tested for combustion performance.
[0069] The amounts of components used in the above Examples 1 to 4 and Comparative Examples 1 to 5 are shown in Table 1.
[0070] Table 1
[0071]
[0072]
[0073] Performance Test:
[0074] The combustion performance was tested using the GJB 770B-2005 method 706.1 target line method.
[0075] Test location: Key Laboratory of Underground Target Destruction, North University of China.
[0076] The test results are shown in Table 2.
[0077] Table 2
[0078]
[0079] In Table 2, I sp is the standard specific impulse, calculated by NASA-CEA2 software, I sp The larger the value, the higher the propellant energy; C* is the characteristic velocity, calculated by NASA-CEA2 software. The larger the value, the higher the propellant energy; T C is the combustion chamber temperature, calculated by NASA-CEA2 software, T C The larger the M, the higher the propellant energy; C is the average molecular weight of the combustion products, calculated by NASA-CEA2 software, M C The smaller it is, the higher the propellant energy is. The burning rate and combustion pressure index are measured values. The test method refers to GJB 770B-2005 method 706.1 target line method. The test location is the Key Laboratory of Underground Target Damage of North University of China.
[0080] The data in Table 2 show that the energy performance of Examples 1 to 4 is basically the same because the mass fraction of the coating layer in the coated aluminum accounts for only 5wt.% of the total mass of the coated aluminum. That is to say, for the coated aluminum, the mass ratio of its coating layer to the metal aluminum is only 5:95. In the formulations of Examples 1 to 4, the amount of coated aluminum added is only 18wt.%. Therefore, for Examples 1 to 4, their formulations are almost the same. Therefore, from a thermodynamic point of view, the energy performance of Examples 1 to 4 is basically the same. For Comparative Examples 1 to 3, what is different from the embodiments is that coated aluminum and DAP-4 are not added to the formulation, but raw materials μAl and traditional nitramine explosives (RDX, HMX or CL-20) are added. The calculation results of Table 2 show that the energy performance of Comparative Examples 1 to 3 is lower than that of Examples 1 to 4. This shows that the introduction of DAP-4 significantly improves the energy performance of hydroxybutyrate propellant, while the use of coated aluminum does not substantially damage the energy performance of the propellant.
[0081] The data in Table 2 also show that the burning rates of Examples 1 to 4 at 7 MPa are significantly higher than those of Comparative Examples 1 to 3 at 7 MPa, while there is no significant difference in their combustion pressure indexes, all within 0.5. This shows that after replacing the "micron aluminum" and "high-energy nitramine explosive" in the traditional HTPB propellant with "coated aluminum" and "DAP-4" respectively, the burning rate of the HTPB propellant is significantly improved under the condition of unchanged mass ratio, and the burning rate at 7 MPa meets the requirements of the high-burning-rate HTPB propellant; this is the result of the combined effect of the coated aluminum powder and DAP-4, not the result of a single factor, that is, the modified HTPB propellant has obvious advantages over the traditional HTPB propellant in terms of kinetics.
[0082] From the data of Comparative Example 4 in Table 2, it can be seen that although the high-energy explosive added to the formula of Comparative Example 4 is DAP-4, since it does not contain coated aluminum powder (raw material μAl is added), its burning rate is improved but still significantly lower than that of Examples 1 to 4.
[0083] From the data of Comparative Example 5 in Table 2, it can be seen that although coated aluminum powder ([nNi+nCu+nFe+nCo] / μAl) is added to the formula of Comparative Example 5, since DAP-4 is not added, its burning rate is still relatively low, which is significantly lower than the burning rates of Examples 1 to 4.
[0084] This once again shows that in the present invention, the improvement of the energy and burning rate of the HTPB propellant is the result of adding the coated aluminum powder and DAP-4, and both are indispensable.
[0085] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which will not affect the essence of the present invention.
Claims
1. A high-energy, high-burning-rate HTPB propellant containing coated aluminum powder and DAP-4, characterized in that: include: The components are in the following mass percentages: 16 wt.% of terminal hydroxyl polybutadiene, 18 wt.% of coated aluminum powder, 54 wt.% of ammonium perchlorate, 10 wt.% of high energy explosive, and 2 wt.% of toluene diisocyanate.
2. The high-energy, high-burning-rate HTPB propellant containing coated aluminum powder and DAP-4 as claimed in claim 1, characterized in that: The coated aluminum powder is μAl coated with nano-Ni, μAl coated with nano-Ni and nano-Cu, μAl coated with nano-Ni, nano-Cu and nano-Fe, or μAl coated with nano-Ni, nano-Cu, nano-Fe and nano-Co.
3. The high-energy, high-burning-rate HTPB propellant containing coated aluminum powder and DAP-4 as claimed in claim 1, characterized in that: The terminal hydroxyl polybutadiene is a binder, and at 25° C., its viscosity is 2 to 4 Pa·s, and its hydroxyl value is 1.5 to 2.0 mmol / g.
4. The high-energy, high-burning-rate HTPB propellant containing coated aluminum powder and DAP-4 as claimed in claim 1, characterized in that: The particle size of the ammonium perchlorate is 100-200 μm.
5. The high-energy, high-burning-rate HTPB propellant containing coated aluminum powder and DAP-4 as claimed in claim 1, characterized in that: The high explosive is DAP-4.
6. A method for preparing a high-energy, high-burning-rate HTPB propellant containing coated aluminum powder and DAP-4 as claimed in claim 1, characterized in that: The following steps are involved: (1) Add an appropriate amount of hydroxy-terminated polybutadiene into a 1L small kneader, start the kneader, and knead slowly; (2) adding an appropriate amount of coated aluminum powder to the kneader, kneading for 10 minutes, then slowly adding an appropriate amount of ammonium perchlorate to the kneader, kneading for 10 minutes, then adding an appropriate amount of high-energy explosive to the kneader, kneading for 10 minutes, then adding a small amount of toluene diisocyanate to the kneader, closing the kneader, evacuating, continuing kneading for 45 minutes, stopping kneading, and ventilating; (3) The kneaded slurry was injected into a square aluminum box and cured in an oven at 60° C. for 15 days to obtain a solid propellant block; (4) Cut the solid propellant block into strips using a cutting machine, and then coat the outer surface of the propellant strips with a layer of polyvinyl alcohol; The above components are taken according to the following mass percentages: 16wt.% of terminal hydroxyl polybutadiene, 18wt.% of coated aluminum powder, 54wt.% of ammonium perchlorate, 10wt.% of high energy explosive, and 2wt.% of toluene diisocyanate.
Citation Information
Patent Citations
Preparation method of multi-element transition metal coated micron aluminum composite fuel
CN114309593A